Discrete Choice Models Applied to Air Transport - Muñoz Hoyos, Claudia Helena (Ingeniería Solidaria, 2014)
This article presents the results of a survey of expressed preferences in a discrete choice experiment, designed to obtain a utility function for airport terminals serving the metropolitan area of the Valle de Aburrá in air passenger transport. The study examined behavior in choosing between the José María Córdoba (jmc) and Enrique Olaya Herrera (eoh) airports for the same destinations. Each was represented in terms of ticket cost, cost of arrival to the airport terminal and travel time to the airport and multinomial logit models were obtained for each Medellín-Bogotá and Medellín-Cali destination evaluated.
Keywords: discrete choice model; airports; air transport; expressed preferences; utility function